Consonant mutation in Nzema and Esahie - Amoh, Samuel; Nyame, John; Nyarko, Isaac; Eshun, Baruch (Linguistik Online, 2023)
This study examines consonant mutation particularly in Esahie[1] and Nzema. The reason for the study arises from the mutuality in the two languages. Again, previous studies have superficially treated this subject in the separate languages. However, the subject of consonant mutation is common in the above languages, yet the prevailing characteristics of the phenomenon are similar and dissimilar in the languages. Thus, this study compares and contrast consonant mutation in the two related languages to establish a correlation. In this vein, it discusses the mutational pattern, directionalities and voicing. Data for this study are assembled from four native speakers of each of the languages and literature of the respective languages. The data are analysed within the purview of Distinctive Feature Theory. The study identifies evidence to the relational effect that, the phonological environments in which the various realizations of mutation occurs also results in a harmony system. However, they differ in their mutational domains. The featural agreement normally forges between the vowel-consonant. Again, it is observed in Nzema and Esahie that, the common feature responsible for mutation in the alternant pairs, [k/x] and [k/g] is [dorsal]; [d/l] and [d/n] is [coronal]; [ʨ/ɕ] is [+strident] and [b/m] is [labial]. In both languages, harmonic assimilation is bidirectional. [1] Esahie is also known as Sefwi, Sehwi, or Asahyue. In Ghana, the language is classified as part of the linguistic Akan group of the larger Akan dialects, even though it shares very close intelligibility with Nzema (a solely ethnographic Akan) than Twi and Mfantse (which are both linguistic and ethnographic Akan). Therefore, in this paper, we shall refer to both variants as separate languages.